Implementation of Educational Programs as a Strategy for Fulfilling Children’s Rights and Reducing Recidivism in Juvenile Correctional Institutions - Patty, Thalia Rizq Aurora; Firmansyah, Hery (Awang Long Law Review, 2025)
This study analyzes the implementation of educational programs as a strategy for fulfilling children's rights and reducing recidivism within the Special Child Development Institution. The right to education is a fundamental mandate of Law No. 11 of 2012 on the Juvenile Criminal Justice System, which ensures that children in conflict with the law continue to receive education, guidance, and skills training as part of their rehabilitation. However, the persistence of juvenile recidivism indicates a gap between legal norms and their practical execution. Employing a qualitative method with both normative juridical and empirical approaches, this research examines the effectiveness of educational program implementation in the Special Child Development Institution. Data were collected through interviews, observations, and a review of legal frameworks and relevant literature. The findings demonstrate that educational programs at the Special Child Development Institution contribute to fulfilling children’s rights by providing access to formal and non-formal education, character development, and vocational training. Nevertheless, their effectiveness in reducing recidivism remains limited due to inadequate facilities, insufficient professional educators, diverse psychosocial backgrounds of the children, and inconsistencies in the educational curriculum. The study affirms that education can serve as a significant instrument for preventing recidivism when supported by structured implementation, consistent mentorship, and strengthened psychosocial interventions. Therefore, optimizing educational programs in the Special Child Development Institution is a strategic step toward ensuring the protection of children’s rights and reducing repeated offending.